2016
DOI: 10.1101/cshperspect.a025049
|View full text |Cite
|
Sign up to set email alerts
|

The Centrosome, a Multitalented Renaissance Organelle

Abstract: The centrosome acts as a microtubule-organizing center (MTOC) from the G to G phases of the cell cycle; it can mature into a spindle pole during mitosis and/or transition into a cilium by elongating microtubules (MTs) from the basal body on cell differentiation or cell cycle arrest. New studies hint that the centrosome functions in more than MT organization. For instance, it has recently been shown that a specific substructure of the centrosome-the mother centriole appendages-are required for the recycling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 129 publications
1
80
0
Order By: Relevance
“…The classic function of the centrosome is to serve as a major microtubule‐organizing center (MTOC) regulating cell cycle progression in animal cells. In addition, it has been shown that the centrosome is involved in immunological synapse formation between T cells and antigen‐presenting cells (Vertii et al , 2016a). Apart from the role in regulating adaptive immunity, a recent study indicates that the centrosome mediates the secretion of cytokines in response to proinflammatory stimuli which induce atypical interphase centrosome maturation in a manner independent of classic mitotic kinase PLK1(Vertii et al , 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…The classic function of the centrosome is to serve as a major microtubule‐organizing center (MTOC) regulating cell cycle progression in animal cells. In addition, it has been shown that the centrosome is involved in immunological synapse formation between T cells and antigen‐presenting cells (Vertii et al , 2016a). Apart from the role in regulating adaptive immunity, a recent study indicates that the centrosome mediates the secretion of cytokines in response to proinflammatory stimuli which induce atypical interphase centrosome maturation in a manner independent of classic mitotic kinase PLK1(Vertii et al , 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that some of the functions of the centrosome depend on the appendages associated with the MC, such as ciliogenesis, cell‐cycle regulation and maintaining the stability of the centrosomal microtubules (Vertii, Hehnly, & Doxsey, ). Dysfunctions of the DAs and SDAs are known to lead to diseases in humans and mice (Bettencourt‐Dias, Hildebrandt, Pellman, Woods, & Godinho, ; Sánchez & Dynlacht, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several hundred proteins are thought to be concentrated in the PCM, and these include proteins involved in nucleating and organizing microtubules (MTs) as well as many important cell-cycle regulators and signaling molecules (Conduit et al., 2015, Vertii et al., 2016). It is unclear, however, how the hundreds of proteins localized within the PCM assemble into a functional organelle.…”
Section: Introductionmentioning
confidence: 99%